Profile of pitolisant in the management of narcolepsy: design, development, and place in therapy - Romigi A; Vitrani G; Lo Giudice T; Centonze D; Franco V (Dove Medical Press, 2018)
Andrea Romigi,1 Giuseppe Vitrani,1 Temistocle Lo Giudice,1 Diego Centonze,1,2 Valentina Franco3 1IRCCS Istituto Neurologico Mediterraneo Neuromed, Pozzilli (IS), Italy; 2Department of System Medicine, University of Rome Tor Vergata Rome, Italy; 3IRCCS Mondino Foundation, Pavia, Italy Abstract: Narcolepsy is a rare sleep disorder characterized by excessive daytime sleepiness and rapid eye movement sleep dysregulation, manifesting as cataplexy and sleep paralysis, as well as hypnagogic and hypnopompic hallucinations. Disease onset may occur at any age, although adolescents and young adults are mainly affected. Currently, the diagnosis delay ranges from 8 to 10 years and drug therapy may only attenuate symptoms. Pitolisant is a first-in-class new drug currently authorized by the European Medicines Agency to treat narcolepsy with or without cataplexy in adults and with an expanded evaluation for the treatment of neurologic diseases such as Parkinson’s disease and epilepsy. This article reviews the pharmacokinetic and pharmacodynamic profile of pitolisant, highlighting its effectiveness and safety in patients with narcolepsy. We performed a systematic review of the literature using PubMed, Embase, and Google Scholar. We report on the efficacy and safety data of pitolisant in narcoleptic patients regarding cataplexy episodes and subjective and objective daytime sleepiness. The development program of pitolisant was characterized by eight Phase II/III studies. One proof-of-concept study followed by two pivotal studies, three randomized controlled trials, and two open studies were evaluated. Our review confirmed the effectiveness of pitolisant in treating major clinically relevant narcolepsy symptoms, including cataplexy, as compared to placebo. In addition, pitolisant revealed a safe profile when compared with placebo and active comparators. Headache, insomnia, and nausea were the prominent side effects. Further long-term randomized controlled trials comparing the efficacy of pitolisant with active comparators (ie, modafinil and sodium oxybate) may clarify its real place in therapy and its possible use as a first-line agent on the basis of its safety and tolerability. Keywords: pitolisant, narcolepsy, cataplexy, histamine, excessive daytime sleepiness